Conjunctival impression cytology in computer users - Kumar, Sanjeev; Bansal, R; Khare, A; Malik, KPS; Malik, VK; Jain, K; Jain, C (Nepalese Journal of Ophthalmology, 2013)
Introduction:It is known that the computer users develop the features of dry eye. Objective: To study the cytological changes in the conjunctiva using conjunctival impression cytology in computer users and a control group. Materials and methods: Fifteen eyes of computer users who had used computers for more than one year and ten eyes of an age-and-sex matched control group (those who had not used computers) were studied by conjunctival impression cytology. Results: Conjunctival impression cytology (CIC) results in the control group were of stage 0 and stage I while the computer user group showed CIC results between stages II to stage IV. Among the computer users, the majority ( > 90 %) showed stage III and stage IV changes. Conclusion: We found that those who used computers daily for long hours developed more CIC changes than those who worked at the computer for a shorter daily duration. Nepal J Ophthalmol 2013; 5(9):33-37 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7819